Deliberations on the External Morphology and Modification of the Labial Segments in the Nepomorpha (Heteroptera: Insecta) with Notes on the Phylogenetic Characteristics - Jolanta Brożek (The Scientific World Journal)
The present study provides new data concerning the external morphology of the labial segments of 46 species from nine Nepomorpha families using the scanning electron microscope. The labial segments are described in detail and images of their structures are presented for the systematic groups. Subsequent segments of the labium (I, II, III, and IV) are shaped similarly in all investigated taxa but carry individual characters in some (sub-)families. Five morphologically distinct forms of the apical plate and five intercalary sclerites have been identified. Additionally, three types of the articulation on the dorsal side between the third and second segments are interpreted as the new characters. The presence of the midventral condyle on the distal edge of the first segment and the third segment has been reanalyzed. New position of the midventral condyle on the proximal edge of the fourth labial segment has been distinguished in several groups. The new set of characters has been estimated from the plesiomorphic taxa of the Nepoidea (Nepidae and Belostomatidae) and subsequently through the more advanced taxa in the relation to the outgroup (Gerromorpha). The evaluation of these characters has revealed twenty-seven new apomorphies for the labium in the Nepomorpha.